2020
DOI: 10.3390/molecules25133021
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hepatocellular-Cancer Activity Exerted by β-Sitosterol and β-Sitosterol-Glucoside from Indigofera zollingeriana Miq

Abstract: Indigofera zollingeriana Miq (I. zollingeriana) is a widely grown tree in Vietnam. It is used to cure various illnesses. The purpose of this study was to investigate the chemical constituents of an I. zollingeriana extract and test its anticancer activity on hepatocellular cells (Huh7 and HepG2). The experimental results of the analysis of the bioactive compounds revealed that β-sitosterol (β-S) and β-sitosterol-glucoside (β-SG) were the main ingredients of the I. zollingeriana extract. Regarding anticancer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Beta-sitosterol is used in traditional medicine in Vietnam. The experimental results in this study revealed that β-sitosterol (β-S) and β-sitosterol-glucoside (β-SG) were the main ingredients of the I. zollingeriana extract 25 . We used the pure extracts of Beta-sitosterol in our study to see the corresponding gene expression alterations in gastric cell lines and found that it increases apoptotic reactions based on concentrations but did not observe the chosen gene alterations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Beta-sitosterol is used in traditional medicine in Vietnam. The experimental results in this study revealed that β-sitosterol (β-S) and β-sitosterol-glucoside (β-SG) were the main ingredients of the I. zollingeriana extract 25 . We used the pure extracts of Beta-sitosterol in our study to see the corresponding gene expression alterations in gastric cell lines and found that it increases apoptotic reactions based on concentrations but did not observe the chosen gene alterations.…”
Section: Discussionmentioning
confidence: 75%
“…In our study, we screened BCL-2, BIRC5, Bax, p53, ABCB1, UHRF1, DNMT1, and HDAC gene activity after the TQ and BS treatment based on possible cell signal transduction pathway. BIRC5 gene activity is regulated by the Hippo BIRC5 pathway, which is an antiapoptotic downstream target gene of the Hippo pathway that plays a role in cell growth and apoptosis 25 . BCL-2 family proteins are the regulators of apoptosis, but also have other functions.…”
Section: Discussionmentioning
confidence: 99%
“…Among bioactive compounds of PM, β-sitosterol, kaempferol, stigmasterol, methyl arachidonate, and quercetin showed strong pharmacological effects. β-Sitosterol, kaempferol, and stigmasterol had obvious antioxidation, antiinflammatory, antitumor, immunoregulation, and metabolic regulation activities (Wilt et al, 2000;Bin Sayeed and Ameen 2015;Devi et al, 2015;Eid and Haddad 2017;Imran et al, 2019;Reyes-Farias and Carrasco-Pozo 2019;Babu and Jayaraman 2020;Bae et al, 2020;Vo et al, 2020). β-Sitosterol interferes with multiple signaling pathways such as cell cycle, proliferation, apoptosis, inflammation, invasion, metastasis, and angiogenesis (Bin Sayeed and Ameen 2015).…”
Section: Discussionmentioning
confidence: 99%
“…β-Sitosterol interferes with multiple signaling pathways such as cell cycle, proliferation, apoptosis, inflammation, invasion, metastasis, and angiogenesis (Bin Sayeed and Ameen 2015). In terms of antitumor, β-sitosterol induced apoptosis by activating caspase-3 and caspase-9 and showed cytotoxic effects on HepG2 and Huh7 cells, but did not have an effect on human primary hepatic fibroblasts (Vo et al, 2020). Kaempferol reduced the risk of skin cancer, liver cancer, and colon cancer by blocking the cell cycle in the G2/M phase, downregulating the related markers of epithelial-mesenchymal transition and accelerating cell necrosis and apoptosis (Imran et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our results with previous investigations we found that the IC 50 of pure TQ against HepG2 was 6.16 µg/mL (El-Najjar et al 2010;Fröhlich et al 2017). In addition, a plant extract isolated from Indigofera zollingeriana also showed low IC 50 values against HepG2 (6.8 ug/ml) and Huh-7 cells (8.7 ug/ml) (Vo et al 2020). However, we can justify their lower IC 50 values compared to ours based on the prolonged contact time between the HCC cells and the plant extract, which was double (48h) the contact time that we applied (24h) in the current study.…”
Section: Effect Of Nanoemulsions On the Cell Antiproliferation Percentagementioning
confidence: 99%